2023
DOI: 10.1039/d2cp04271a
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the different effects of 4d-transition metals on the performance of Li-rich cathode Li2MnO3 by first-principles

Abstract: The poor cycle performance of Li-rich cathode Li2MnO3, a promising cathode of the next-generation Li-ion batteries, limits its commercial applications. Transition metal (TM) doping is widely applied to optimize the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The Li vacancy formation energy in undoped Li 2 MnO 3 is determined to be within the range of 4.53-4.70 eV, exhibiting excellent agreement with other computationally derived results. 21,58 For Mg-doped Li 2 MnO 3 , we observe a significant reduction in the formation energies of Li vacancies surrounding the Mg dopant. The lowest formation energy is found for the Li vacancies at the We then calculate the average delithiation voltage in different delithiation stages according to the following equation: 59…”
Section: Delithiation Voltagementioning
confidence: 83%
See 2 more Smart Citations
“…The Li vacancy formation energy in undoped Li 2 MnO 3 is determined to be within the range of 4.53-4.70 eV, exhibiting excellent agreement with other computationally derived results. 21,58 For Mg-doped Li 2 MnO 3 , we observe a significant reduction in the formation energies of Li vacancies surrounding the Mg dopant. The lowest formation energy is found for the Li vacancies at the We then calculate the average delithiation voltage in different delithiation stages according to the following equation: 59…”
Section: Delithiation Voltagementioning
confidence: 83%
“…Elemental substitution or atomic doping has been commonly employed to enhance the cycling performance and maintain the capacity of Li-rich LIBs. 19,20 Transition metals are widely chosen as dopants and have been extensively studied, [21][22][23][24][25][26] but alkali earth metal doping has also received attention in recent years. It is generally recognized that adding Mg atoms into Li-rich cathode materials has a positive effect on the electrochemical performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This work selected four transition metals, Ni, Co, Ru and Cr, for doping Li 2 MnO 3 at the Mn site. Extensive research has been done on the doping of Ni, 35−40 Co, 39−41 Ru, 38,40,42 and Cr 41,43,44 into LMO. A density functional theory (DFT) + U study presented by Lanjan et al 39 showed that replacing 50% Mn with Ni or Co reduces the band gap and consequently increases the conductivity of Li 2 Mn 0.5 TM 0.5 O 3 .…”
Section: Introductionmentioning
confidence: 99%
“…This work selected four transition metals, Ni, Co, Ru and Cr, for doping Li 2 MnO 3 at the Mn site. Extensive research has been done on the doping of Ni, Co, Ru, ,, and Cr ,, into LMO. A density functional theory (DFT) + U study presented by Lanjan et al .…”
Section: Introductionmentioning
confidence: 99%